Innate immune cell infiltration in melanoma metastases affects survival and is associated with BRAFV600E mutation status. Issue 1 (February 2019) - Dabrosin, Nina; Sloth Juul, Karen; Bæhr Georgsen, Jeanette; Andrup, Simon; Schmidt, Henrik; Steiniche, Torben; Heide Øllegaard, Trine; Bønnelykke Behrndtz, Louise
Abstract : Little is known about the infiltrative pattern of innate immune cells in primary melanoma compared with their paired metastases and in BRAF V600E -mutated tumors. Therefore, our aim was to characterize the inflammatory microenvironment in primary ulcerated and nonulcerated melanomas and paired metastases, to investigate the relation between inflammation and BRAF V600E mutation in primary melanoma and paired metastases, and to evaluate the effect of the analyzed biomarkers on melanoma-specific survival. A total of 385 primary tumors and 96 paired metastases were stained with immunohistochemistry for BRAF V600E, CD163+ macrophages, CD123+ plasmacytoid dendritic cells, CD66b+ neutrophils, and E-cadherin and estimated using objective computer-assisted image analysis. BRAF V600E was semiquantitatively scored as either present or absent. In metastases of nonulcerated melanomas, we observed higher neutrophil ( P =0.02) and macrophage ( P =0.01) numbers. In the metastases of ulcerated melanomas, we found a higher number of macrophages ( P <0.0001). Increase in the neutrophil numbers in the metastases was associated with poor patient survival after first relapse (hazard ratio=1.19, 95% confidence interval: 1.03–1.38, P =0.02). BRAF V600E -positive primary tumors ( P =0.02) and metastases ( P =0.01) exhibited increased plasmacytoid dendritic cell numbers compared with BRAF V600E -negative tumors. Lastly, primary melanomas in men had higher neutrophil numbers than women ( P ⩽0.0001), and men had worse melanoma-specific survival (hazard ratio=1.52, 95% confidence interval: 1.04–2.21, P =0.03). Our data show that melanoma metastases are densely infiltrated with neutrophils, which affects survival. Our results also highlight the importance of recognizing the presence of inflammatory cells in the metastases as a prognostic marker, and that they may potentially be used to improve the precision of immunotherapy and BRAF V600E targeted therapy.